KONSEP GURU DALAM PENDIDIKAN ISLAM DITINJAU DARI PERSPEKTIF AL-QUR’AN - Arif, Fadli; Yuliane, Yuliane; Krisnawati, Ike; Hendrizal, Hendrizal; Manovtri, Reni (Al-Isyraq: Jurnal Bimbingan, Penyuluhan, dan Konseling Islam, 2024)
This research aims to describe the concept of teachers in Islamic education from the perspective of the Holy Quran. The method used in this research is a qualitative method with a literature study approach. The results of this research show that a teacher is someone who is responsible for guiding, directing and being a role model for their students. Teachers have the most important responsibility and role, because a teacher must be able to direct and guide students so that they have intelligence and good manners that will be implemented in carrying out their lives. In Islamic education, teachers do not only convey their knowledge, but as educators they must also be responsible for the development of their students’ behavior so that morals are formed.